Ciri Makroskopis, Kekerasan dan Berat Jenis Fosil Kayu Asal Desa Purwajaya Kutai Kartanegara - Robin Sulistyo; Nani Husien; Erwin Erwin; Agus Sulistyo Budi (Fakultas Kehutanan Universitas Mulawarman, 2021)
The results showed that macroscopically the studied wood fossils had brick red, gray, yellow, brown, and black in the first sample (FKA), and the second sample (FKB) had white, gray, and light brown colors, which this color difference was probably due to the cells being mixed with other inorganic elements even though they were found in adjacent locations. Another observation of the macroscopic features of the two samples indicated that cells were still obviously visible as on normal wood, such as pores, rays, and axial intercellular canal. Based on the characteristics of AIC, it was found to have general features that were often found in several types of wood in the Dipterocarpaceae family. The results of measuring the hardness value, the two fossil samples have the same hardness value, namely 4 Mohs scale. For the meantime, the specific gravity of the FKA and FKB samples were 2.54 and 2.35, respectively.